2008
DOI: 10.1080/10824660802427710
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Early Vocabulary for Literacy Achievement in High-Poverty Schools

Abstract: Although research documents a key contribution of print skills to early literacy, vocabulary and other language skills also provide an important foundation. Focusing on a sample of several hundred low-income children in 16 urban schools that were implementing literacy interventions, 1st-grade predictors of literacy development were traced over time. Beginning-of-1st-grade letter-word identification and word attack skills were the strongest predictors of reading comprehension at the end of 1st grade. However, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 41 publications
(42 reference statements)
3
37
0
5
Order By: Relevance
“…Hemphill and Tivnan (2008) used the PPVT to assess English receptive vocabulary in low SES emergent bilingual Spanish-English children over a set period of time. The children obtained a mean SS of 87 on the PPVT at the beginning of the first grade; a score that was nearly one standard deviation below the norm (placing the learners at the 19th percentile) and which was considered to be an indication of weak vocabulary skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hemphill and Tivnan (2008) used the PPVT to assess English receptive vocabulary in low SES emergent bilingual Spanish-English children over a set period of time. The children obtained a mean SS of 87 on the PPVT at the beginning of the first grade; a score that was nearly one standard deviation below the norm (placing the learners at the 19th percentile) and which was considered to be an indication of weak vocabulary skills.…”
Section: Discussionmentioning
confidence: 99%
“…Hemphill and Tivnan (2008) and Scarborough (2001) 1. the majority of the learners studied have not acquired vocabulary skills in their L2 (English) to such an extent that L2 vocabulary could be measured expressively 2. most aspects of PA were so poorly developed in this sample that it was difficult to assess PA skills 3. the majority of the learners have not started to decode text.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemphill and Tivnan (2008) suggest that a child's early vocabulary is strongly correlated with his later reading comprehension skills. This idea is supported by a study by Missal et al (2007) who found that "any attempt to increase a student's early literacy skills with respect to language, rhyming, and alliteration should result in positive shifts in that student's later reading skills (p. 446).…”
Section: School Environmentmentioning
confidence: 99%